IMPROVING STUDENT LEARNING OUTCOMES BY USING THE SPIDER WEBBED MODEL IN THEMATIC LEARNING TOWARDS FOURTH GRADE STUDENTS OF SDN KALIASIN V/284 SURABAYA ACADEMIC YEAR 2021/2022 - Wiwik Sugiarti (LPPM STAI Muhammadiyah Probolinggo, 2022)
This study is to describe the Application Of The Profit Webs Model In Improving Learning Outcomes Of The Environmental Subtema Students Class IV SDN Kaliasin V/284 Surabaya Academic Year 2021/2022. The type of classroom action research used in this research is collaborative research. The action in this research is the application of the spider web model which aims to improve the learning outcomes of fourth grade students with the sub-theme of friends' environment. This research was conducted in two cycles. Cycle 1 consists of 2 meetings and Cycle 2 consists of 2 meetings. The actions of Cycle 1 and Cycle 2 are carried out according to the plan set out in the RPP. The results showed that after applying the spider web model to the friend-environment subtheme and taking action, the learning pattern could be improved effectively so as to produce student learning outcomes which were marked by the mastery of learning outcomes in each cycle. can be improved. This success is the result of applying the spider web model by teaching key concepts that keep students active and make learning fun. This means that students are more likely to actively participate in the teaching and learning process given by the teacher and discuss and ask questions in class. Learning outcomes data collected during Cycles I and II showed that students experienced an increase. The results of the first cycle test were 13 students or 52% completed and 12 students or 48% incomplete. The results of the second cycle test then showed that 22 students or 88% completed and 3 students or 12% did not. This learning improvement is considered successful with an increase in students reaching 88% of students and exceeding the success index of 75%